Relating 2D isovists to audiovisual assessments of two urban spaces in a neighbourhood - Llorca-Bofí Josep; Heck Jonas; Vorländer Michael (Noise Mapping, 2024)
In the field of urban design assessment, increasing attention to the nonexpert verbalizations is paid to engage social participation in planning processes, especially those not limited to static visual renderings. However, little has been explored on reproducible methods to collect these vocabularies and their relationship with architectural features. This study presents a hierarchical multifactor analysis to extract the main perceptual nonexpert clusters; and a linear correlation analysis to relate them with 2D isovist measures. In an on-line experiment, participants (n=20n=20) elicited individual attributes (n=120n=120) to describe their soundscape and visual perception and compared recorded urban environments (n=8n=8). The results show that a percentage of nonexpert audio attributes correlate as well as the visual ones with isovist metrics.